2008
DOI: 10.1007/s12043-008-0136-7
|View full text |Cite
|
Sign up to set email alerts
|

Deformed special relativity with an invariant minimum speed and its cosmological implications

Abstract: It will be introduced a new symmetry principle in the space-time geometry through the elimination of the classical idea of rest, by including a universal minimum limit of speed in the subatomic world. Such a lowest limit, unattainable by particles, represents a preferred reference frame associated with a universal background field that breaks Lorentz symmetry. Thus the structure of space-time is extended due to the presence of a vacuum energy density, which leads to a negative pressure at cosmological length s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(43 citation statements)
references
References 11 publications
2
41
0
Order By: Relevance
“…(43). In summary, we have shown that there is a tiny dimensionless coupling constant (ξ = V /c ∼ 10 −22 ) that couples gravity with electromagnetic fields, where V (∼ 10 −14 m/s) is the universal minimum speed related to a preferred background frame (Section 5), which is associated to a uniform background field with low vacuum energy density connected to the cosmological "constant" Λ[11] [13]. This connection between Λ and V can already be obtained directly from Eq.…”
Section: Dirac's Lnh and The Coupling Constant ξmentioning
confidence: 99%
See 2 more Smart Citations
“…(43). In summary, we have shown that there is a tiny dimensionless coupling constant (ξ = V /c ∼ 10 −22 ) that couples gravity with electromagnetic fields, where V (∼ 10 −14 m/s) is the universal minimum speed related to a preferred background frame (Section 5), which is associated to a uniform background field with low vacuum energy density connected to the cosmological "constant" Λ[11] [13]. This connection between Λ and V can already be obtained directly from Eq.…”
Section: Dirac's Lnh and The Coupling Constant ξmentioning
confidence: 99%
“…(43), where V ∝ √ G. The background field energy density ρ (2) em brings a new aspect of gravitation that needs to be thoroughly investigated. This new feature brings with it a change in our notion of space-time and, thus, also the concept of inertial frames (galilean frameworks) with regard to the motion of subatomic particles [11][12] [13]. This subject will be investigated in the next section.…”
Section: Dirac's Lnh and The Coupling Constant ξmentioning
confidence: 99%
See 1 more Smart Citation
“…Now, we note that Lorentz symmetry breaking due to the presence of the ultrareferential S V connected to the dark energy that fills the sphere has origin in a nonclassical (nonlocal) aspect of gravity that leads to a repulsive gravitational potential (φ < 0). In order to see such an anti-gravity, let us consider the total energy of a proof particle on the surface of such a dark sphere according to SSR, [5][6][7] namely, from where we obtain…”
Section: Ssr-metric and Ds-metricmentioning
confidence: 99%
“…4 Symmetrical Special Relativity (SSR) is a theory that has recently appeared [5][6][7][8][9] as a new candidate for describing gravitational vacuum, from where it has already been possible to calculate the value of the cosmological constant and also discusses the origin of the uncertainty principle. 8 SSR is a kind of theory of deformed special relativity (DSR) with double limit of speeds, namely, a maximum limit of speed c (speed of light) and a minimum speed V .…”
Section: Introductionmentioning
confidence: 99%